Incarcerated Larrey hernia with small bowel obstruction: A case report. (March 2023) - Sasaki, Noriyuki; Mitomo, Shingo; Matsui, Yusuke; Ishii, Yugo; Sasaki, Akira
Abstract: Introduction and importance: Morgagni–Larrey hernias (MLHs) are rare diaphragmatic hernias that can cause incarceration or strangulation of the hernia contents in some cases. Here we report a case of incarcerated Larrey hernia with small bowel obstruction, which was successfully treated with emergent laparoscopic surgery. Case presentation: An 87-year-old woman presented to our hospital with abdominal pain and nausea. Computed tomography scan revealed an MLH comprising an obstructed intestinal loop. The patient underwent emergency laparoscopic surgery. Surgical findings showed incarceration of the small bowel on the left side of the falciform ligament. The small bowel was laparoscopically reduced and does not show signs of intestinal ischemia or perforation. The hernia orifice, which was approximately 15 mm in diameter, was closed with a surgical suture without the need for sac excision. The patient was discharged on postoperative day 7 without postoperative complications. Clinical discussion: There are no established surgical techniques for the treatment of MLH due to its rarity. Our experience in the present case suggests that the laparoscopic approach might be considered as a feasible method even for incarcerated MLH. Conclusion: Surgical techniques for MLH should be selected on a case-by-case basis. Highlights: Morgagni–Larrey hernias (MLHs) are rare diaphragmatic hernias. MLHs can lead to the incarceration or strangulation of hernia contents. Surgical techniques for MLHs are selected on a case-by-case basis. Laparoscopic approach might be useful for incarcerated or strangulated MLHs.